Genetic Transformation of Rice Cultivars Using Particle Bombardment for Salinity Tolerance - Htwe, Nwe Nwe (2011)
Rice is one of the major cereal crops and stable food for feeding more than half of world population. Now we are facing with some problems for rice production and it must be increased by 60% for next 20 years. Also 30% of rice growing area in the world contains high salt to allow normal yield. Salinity stress is severely limited the plant growth and productivity. The main problem in rice growth and productivity are unfavourably affected by salt stress. Na+ and Cl- derived from NaCl salts contaminate the soils, which are well known as the toxic ions that damage the plant cells in ion homeostatis and osmotic effect. Genetic transformation has widely been considered as a tool for crop improvement. Transient gene expression system is a critical requirement for target gene into cell and easy for analysing the function of a particular gene. This study was mainly aimed to establish a suitable in vitro culture system under salinity condition of selected five Malaysin rice genotypes as well as to introduce the delta 1 Pyrroline five carboxylase (P5CS) cDNA into rice genome using particle bombardment. This present study has highlighted some interesting findings as described below: Callus induction is one of the significant steps for selection of suitable genotypes and identifies the most suitable medium. In this study, five selected Malaysian rice genotypes were used and investigated for in vitro salt stress responses. All genotypes showed that the callus-growth capacities were significantly affected by the genotypes and the culture medium. Markedly, callus was best induced on the MS medium added with 10μM 2,4-D and 0.4gm/L casein hydrolysate. The shoot regeneration capacity was the most effective in half MS strength with 10μM BAP. The genotype, MR219-4, consistently performed the best in callus induction (93.5%) as well as in plant regeneration (27%). However under salinity condition, it showed a decline in callus growth, regeneration capacity and proline accumulation. This genotype can be a good model system for studying the genetic transformation. For genetic transformation, antibiotic resistance genes are routinely used as powerful markers for selection of transformed cells. The minimun inhibitory level of hygromycin concentration was optimized for selected mutant rice line and it was showed that 21.3% calli survived on the medium containing 45 mg/L hygromycin. Transient expression of gfp and gus gene mediated by particle bombardment is rapid and provide useful approach for visual monitoring of genetic transformation. All the results indicated that gfp gene expression is superior to gus gene expression. The optimised conditions were bombardment once at a helium pressure of 1100psi, 6cm target tissue distance, 27 inHg vacuum pressure, 1μm gold particle size and 1.5μg DNA concentration per bombardment. These optimized conditions have been used to obtain stably transformed explants for subsequent regeneration. Sixteen transgenic rice plants expressing gfp gus and hptII transgene were obtained from MR219-4 and transformation efficiency was 2.5% for hptII, gfp and gus. The pBIP5CS plasmid includng P5CS (Δ 1-pyrroline-5-carboxylate synthetase catalyses the first two steps of proline biosynthesis) cDNA encoding hptII gene conferring resistance to hygromycin was transformed to rice callus. The resultant primary transgenic plants showed more proline accumulation than non-transformed plant and transformation efficiency was 2.1%. Nine plants regenerated from hygromycin containing medium and were molecularly characterized by using PCR, RT PCR (Reverse transcriptase) and Southern Blot analysis. The result showed that P5CS cDNA had been integrated into six transgenic rice lines and proline level was increasing nine fold compared with non-transformed plants in 250mM NaCl stress. All these lines will be integrated into breeding programs for further assessment of their benefits.